An economic evaluation of kinnow cultivation in north western India - YOGI, VIKRAM; KUMAR, PRAMOD; PRAKASH, P; KAR, AMIT; SINGH, D R; SINGH, RASHMI; ARYA, PRAWIN; AWASTHI, O P (The Indian Journal of Agricultural Sciences, 2019)
The present study analysed the primary data collected from 180 randomly selected kinnow growing farmers of three districts of Haryana and Punjab during the year 2016–17. It was revealed that kinnow cultivation in north western India has advantage over the traditional wheat-cotton farming; yielding 121.33% higher net return per ha. Kinnow cultivation involved lesser investment on irrigation, fertilizer and plant protection chemicals, but generated 12.78% higher employment than that of wheat-cotton farming system. Kinnow cultivation has proved out to be a viable enterprise. This is, therefore, empirically proven that it is a suitable option to diversify from the prevailing rice-wheat cropping system in certain parts of north western India.